A review of uphill and downhill running: biomechanics, physiology and modulating factors - Lu, Zeyu; Suo, Bokai; Deng, Liqin; Wang, Jichao; Fu, Weijie; Zhong, Yunjian; Jin, Jing (Frontiers in Bioengineering and Biotechnology, 2025)
Graded running imposes distinct biomechanical and physiological demands compared with level running, which influences performance outcomes and injury risk. Uphill running requires great propulsion and energy expenditure, which results in increased oxygen consumption and cardiovascular burden. By contrast, downhill running relies heavily on eccentric muscle contractions, which show an association with great fatigue and a high risk of injury. This review aims to summarize biomechanical and physiological adaptations to uphill and downhill running and evaluate the mechanisms underlying the interaction of modulating factors (footwear, foot strike patterns, individual characteristics, pacing strategies, cadence and running speed) with slope. Based on current evidence, these factors affect mechanical loading, energy cost and neuromuscular responses during uphill and downhill running. Footwear design, especially carbon-fiber plate shoes, can reduce metabolic cost during uphill and downhill running. Forefoot striking reduces peak impact forces compared to rearfoot striking, especially in downhill running, helping to lower impact on the lower limbs. Individual factors, like training level, influence the effectiveness of these factors, with experienced runners adapting better to slopes. Additionally, adjusting cadence can reduce per-step load and energy expenditure during uphill and downhill running. Although considerable progress has been made, further research still necessitates the exploration of graded running in real-world environments, improvement of training methods, clarification of the interactions between various factors and slope and optimization of methods to prevent injuries.